Addressing Soil Salinity Stress in Rice Farming: Insights from Tirtayasa District, Banten Province, Indonesia - Hasrianda, Erwin Fajar (Perum BULOG, 2024)
Soil salinity stress poses a major obstacle to rice farming and food security in Indonesia, especially in the Tirtayasa sub-district, Banten Province. This condition is exacerbated by climate change and global warming. A field study was conducted to examine the impact of salt stress on rice farming and gain insights from farmers in salin-affected areas to develop salt-tolerant rice varieties. The research included measurements of soil salinity levels, soil pH, visual documentation of rice plant health, and microscopic observations. The results showed an increasing land area affected by salt stress over the years in the Tirtayasa region. Morphological analysis indicated that Inpari 32 rice plants exposed to salinity had fewer roots, even at moderate salinity levels, resulting in a significant decrease in yields up to 100 percent. Farmers also lacked effective methods to cope with salt stress in their fields. Although the market provides salt-tolerant rice cultivars, farmers observe that their yields are not comparable to non-tolerant varieties. This study highlights the urgency of developing salt-tolerant rice varieties in line with the preferences of local farmers to enhance food resilience in Indonesia. These findings provide additional information on salin soil in Banten and the need to develop a salt-tolerant rice variety to overcome salin-stress challenges in agriculture.